Efficacy of clopidogrel treatment and platelet responsiveness in peripheral arterial procedures. (October 2014) - Spiliopoulos, Stavros; Pastromas, George; Diamantopoulos, Athanasios; Katsanos, Konstantinos
<x xml:space="preserve">Abstract</x> Introduction: Long-term antiplatelet therapy with clopidogrel has been recommended in patients undergoing peripheral arterial procedures. Poor antiplatelet effect of clopidogrel or high on-clopidogrel platelet reactivity (HCPR) has been recently identified in patients with peripheral arterial disease (PAD). Areas covered: This review focuses on the use of clopidogrel and the phenomenon of HCPR in PAD patients treated for intermittent claudication or critical limb ischaemia (CLI). The authors summarize current guidelines and recommendations for use of clopidogrel following peripheral arterial procedures and explore the prevalence and clinical impact of HCPR in the PAD population. Underlying mechanisms of HCPR and relevant clinical and genetic factors are analyzed with particular attention to the potential utility of point-of-care platelet function testing (PFT). Expert opinion: Clopidogrel is a safe, effective and well-tolerated antiplatelet agent in PAD patients following peripheral arterial revascularization. Dual-antiplatelet therapy could also be considered after complex endovascular procedures. HCPR has been identified in more than 50% of PAD patients on clopidogrel and has been related with significantly increased re-intervention rates. Incidence of HCPR is significantly higher in patients with CLI, diabetes mellitus and chronic renal disease. Personalized antiplatelet therapy on the basis of PFT is an elegant emerging concept for optimization of platelet inhibition and potential identification of patients at increased risk of bleeding and warrants investigation in future large-scale trials.